Recombinant IgG1 Fc hexamers block cytotoxicity and pathological changes in experimental in vitro and rat models of neuromyelitis optica - Tradtrantip, Lukmanee; Felix, Christian M.; Spirig, Rolf; Morelli, Adriana Baz; Verkman, A.S. (Neuropharmacology, 2018)
Intravenous human immunoglobulin G (IVIG) may have therapeutic benefit in neuromyelitis optica spectrum disorders (herein called NMO), in part because of the anti-inflammatory properties of the IgG Fc region. Here, we evaluated recombinant Fc hexamers consisting of the IgM μ-tailpiece fused with the Fc region of human IgG1. In vitro, the Fc hexamers prevented cytotoxicity in aquaporin-4 (AQP4) expressing cells and in rat spinal cord slice cultures exposed to NMO anti-AQP4 autoantibody (AQP4-IgG) and complement, with >500-fold greater potency than IVIG or monomeric Fc fragments. Fc hexamers at low concentration also prevented antibody-dependent cellular cytotoxicity produced by AQP4-IgG and natural killer cells. Serum from rats administered a single intravenous dose of Fc hexamers at 50 mg/kg taken at 8 h did not produce complement-dependent cytotoxicity when added to AQP4-IgG-treated AQP4-expressing cell cultures. In an experimental rat model of NMO produced by intracerebral injection of AQP4-IgG, Fc hexamers at 50 mg/kg administered before and at 12 h after AQP4-IgG fully prevented astrocyte injury, complement activation, inflammation and demyelination. These results support the potential therapeutic utility of recombinant IgG1 Fc hexamers in AQP4-IgG seropositive NMO. •Neuromyelitis optica (NMO) is an autoimmune inflammatory disease of the central nervous system.•Recombinant Fc hexamers, consisting of the IgM μ-tailpiece fused with the Fc region of human IgG1, were studied for treatment of NMO.•Fc hexamers inhibited complement- and cell-mediated cytotoxicity caused by NMO autoantibody in vitro and prevented NMO pathology in a rat model of NMO.